Hubungan Motivasi Berprestasi, ( English ) Self Efficacy dan Jenis Kelamin dengan Prestasi Belajar Bahasa Inggris Siswa Kelas XII MAN Salatiga - Nurjadid, Nurjadid (Faculty of Teacher Training and Education of Undaris, 2017)
The aim of this research is to find out the relation of achievement motivation, English self efficacy and sex with English Learning Motivation Achievement of Student Grade 12th English at MAN Salatiga. The population in this research is the whole students of grade 12th which amounts 295 students, while the number of the samples that has been used in this research were 100 students. To measure the achievement motivation it has been used questionnaire adapted by McLelland (dalam Wijono, 2012). To measure the variable of English self efficacy it has been used questionnaire by Corsini (dalam Siregar, 2012), while the student’s achievement has been measured by using the mid test in the second semester period 2013/2014. Before testing the hypothesis, first, it is measureed the validity and reliability of measuring instruments by using a standard p<0.05 for validity and p<0.05 for reliability. After the writer/researcher test the hypothesis, then there are some research results as follows: there is no a significant relationship of achievement motivation and English self efficacy with student achievement, there is no interaction effect of peer achievement motivation and sex with student achievement, there is no interaction effect of English self efficacy and sex with student achievement, the population rates there was no difference in student learning achievement in terms of gender.